THE INFLUENCE OF GOAL ORIENTATION, FEEDBACK ORIENTATION, AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT MASABARU GUNAPERSADA IN SURABAYA - Tofan Eka Wardhana; Sri Rahayu; Sundjoto; Rifda Fitrianty (RADJA PUBLIKA, 2025)
This study aims to analyze the effects of Goal Orientation, Feedback Orientation, and Work Environment on employee performance at PT. Masabaru Gunapersada in Surabaya. The research employs a quantitative method with an associative approach. The population of this study consists of all employees of PT. Masabaru Gunapersada in Surabaya, totaling 56 employees, and the entire population is used as the research sample through a census sampling technique. Data collection was conducted by distributing questionnaires using a Likert scale. The data analysis techniques include data quality testing, classical assumption tests, multiple linear regression analysis, partial tests, simultaneous tests, and coefficient of determination analysis, with the assistance of SPSS software. The results show that Goal Orientation and Work Environment partially have a significant effect on employee performance, while Feedback Orientation partially does not have a significant effect on employee performance. Simultaneously, Goal Orientation, Feedback Orientation, and Work Environment have a significant effect on employee performance, with Work Environment being the most dominant variable influencing employee performance at PT. Masabaru Gunapersada in Surabaya.